Pemanfaatan Teknologi Digital Dalam Pembelajaran Untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Rohmah, Sindi Sifaur (Indonesian Journal of Islamic Educational Review, 2025)
Education in the digital era significantly changes the learning carried out. Digital technology has also become a part of the daily lives of junior high school students, and its utilization in the context of learning can bring great benefits, especially in developing students’ critical thinking skills. This study aims to explain how the use of digital technology in education can improve the critical thinking skills of junior high school students. Critical thinking skills are the student’s ability to analyze, evaluate, and interpret information critically and logically. This study used a qualitative descriptive approach to collect data from various sources, including related research, literature, and case studies. The results showed that the use of digital technology in learning can provide an environment that supports the development of junior high school students' critical thinking skills.